Consumer Satisfaction in Islamic Economic Perspective: A Literature Review on Product and Service Quality - Saifur Rahman; UmpuSInga, Hasrun Afandi; Iskandar Ali Alam; Andala Rama Putra Barusman; Habiburahman (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2026)
Consumer satisfaction in Islamic economic perspective is not merely measured by the fulfillment of consumer expectations, but also by compliance with Islamic ethical values and the achievement of public benefit (maṣlaḥah). This article aims to examine consumer satisfaction through a literature review by integrating product quality and service quality within the framework of Islamic economics. The study emphasizes key Islamic principles such as ṣidq (honesty), amānah (trustworthiness), and ‘adl (justice) in service delivery, as well as the concept of halālan ṭayyiban in product quality. Furthermore, consumer satisfaction is analyzed using the perspective of maqāṣid al-syarī‘ah to ensure that business practices contribute to the protection of religion, life, intellect, lineage, and wealth. The findings indicate that product quality and service quality significantly influence consumer satisfaction when they are aligned with Islamic ethical values and normative principles. This study contributes theoretically by enriching the discourse of consumer satisfaction in Islamic economics and practically by offering ethical guidelines for business practices in sharia-compliant institutions.